2018
DOI: 10.1101/284158
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic Construction of Reduced Representations in the Brain for Perceptual Decision Behavior

Abstract: Current models propose that the brain uses a multi-layered architecture to reduce the high dimensional visual input to lower dimensional representations that support face, object and scene categorizations. However, understanding the brain mechanisms that support such information reduction for behavior remains challenging. We addressed the challenge using a novel information theoretic framework that quantifies the relationships between three key variables: single-trial information randomly sampled from an ambig… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 62 publications
0
42
0
Order By: Relevance
“…As shown by Chang et al [36], neurons selectively respond along a single axis of the face space, not to other, orthogonal axes. An interesting direction of research is to determine whether our reduced diagnostic features, as defined by our 'abstract information goal' (see also [37]), provide a superior fit to the neural data than the full feature sets used in the axis model used by Chang et al [36] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by Chang et al [36], neurons selectively respond along a single axis of the face space, not to other, orthogonal axes. An interesting direction of research is to determine whether our reduced diagnostic features, as defined by our 'abstract information goal' (see also [37]), provide a superior fit to the neural data than the full feature sets used in the axis model used by Chang et al [36] .…”
mentioning
confidence: 99%
“…as representation in multi-scale, multi-orientation Gabor-like, retinotopically mapped receptive fields [38,39]; at intermediate levels of processing, as the sort of local surface patches [40,41] that we reveal, and at the top level as the combinations of surface patches that enable identification and resemblance responses. Under a framework of top-down prediction [42,43], the abstract information goal of a familiar face identity should trim, in a top-down manner, the fully-mapped but redundant information on the retina into the task-relevant features that are transferred along the occipital to ventral/dorsal visual hierarchy [37]. Tracing the construction of such a reduced memory representation of face identity in the brain should enable an accurate and detailed modelling of the processing mechanism along the visual hierarchy (see also [12,[44][45][46]).…”
mentioning
confidence: 99%
“…Despite the same experimental stimuli, this gating phenomenon is only seen in the gender task, suggesting that it is specific to lateralized task-relevant features (the eyes being used almost exclusively for the gender task). In a recent study, the N170 also appeared to filter out task-irrelevant features: while both task-relevant and task-irrelevant features were processed prior to 170 ms, only taskrelevant features were processed afterwards 37 . Of note, the cause of this gating cannot be repetition priming because it is also visible in trials where only one feature is revealed once.…”
Section: Discussionmentioning
confidence: 99%
“…Applying SIR to understand visual information processing SIR has been recently applied to analyze brain imaging data collected during the performance of a visual categorization task 22 . This study illustrates how the SIR framework can be used to disentangle brain activity into the processing of task-relevant stimulus information, the processing of task-irrelevant stimulus information, and other brain processes, to enrich the interpretation of brain imaging data.…”
Section: The Sir Frameworkmentioning
confidence: 99%
“…Zhan et al 22 used these three SIR components to trace the dynamic flow of taskrelevant features that were processed between 50 and 220 ms post stimulus, from their early representation in the visual cortex, through the ventral pathway. In the ventral pathway, we found that task-relevant features converge onto a few MEG voxels at the top of the right fusiform gyrus, ~200 ms post-stimulus, where they agglomerate into distinct representations that support each behavioral decision (see "task-relevant" images in Figure 2C).…”
Section: The Sir Frameworkmentioning
confidence: 99%